THE ISLAMIC CONCEPT OF FACILITIES IN GRAND KALIMAS SHARIA HOTEL SURABAYA BASED ON MUHAMMAD RAYHAN JANITRA’s PERSPECTIVE - Fitriyah Fitriyah (Dirosatuna: Journal of Islamic Studies, 2021)
One of the trends in halal tourism concept in sharia hotel services, considering the paradigm of the society regarding to whereabouts of hotels meant for negative things such as adultery, wassail, indiscretion, and so on. The society believes that the availability of this sharia hotel is an effort to minimize the existence of immoral practices that are rife. The existence of sharia values within sharia hotel facilities is able to be business field that upholds the sublime values of religion so that it can provide the common good to the wider community. This study is a qualitative research that aims to answer the questions about how the facilities available at Grand Kalimas Sharia Hotel Surabaya in terms of Islamic Economics. The tool used to analyse this study is the six basic principles of Islam in the hospitality business based on Muhammad Rayhan Janitra’s ideas, they are; the principles of cunsumption, the principles of entertainment, the principles of ethic, the principles of business activities, the principles of relationship boundaries, and the principles of disposition. The thought pattern used in this analysis is inductive reasoning. And the data collection techniques used in this study are interviews with the hotel’s stakeholders, observations, and documentation. The result of this research is that the hotel is trying to make hotel facilities easier for muslim guests to worship, such us; provision of prayer equipment in the bedroom, purification media in the bathroom and toilet, a direction of Qibla, as well as the establishment of Islamic events. In its entirety, the facilities available at Grand Kalimas Sharia Hotel Surabaya are good at applying sharia principles of hospitality business, but less than maximum in applying the principles of relationship boundaries in Front Office area, public toilet, and musalla. The obstacles faced are the lack of awareness of the hotel to put up the written directive for muslim guests to be dressed neatly and covered so it creates a less Islamic atmosphere in the hotel area, and limited land of the hotel so it doesn’t allow the provision of partition-wall between urinals in the toilet and it created a mingling of male and female guests worshipping in musalla.